Antimicrobial activities of the methanol extract and compounds from Artocarpus communis (Moraceae) - Kuete, Victor (BioMed Central, 2011)
BACKGROUND: Artocarpus communis is used traditionally in Cameroon to treat several ailments, including infectious and associated diseases. This work was therefore designed to investigate the antimicrobial activities of the methanol extract (ACB) and compounds isolated from the bark of this plant, namely peruvianursenyl acetate C (1), α-amyrenol or viminalol (2), artonin E (4) and 2-[(3,5-dihydroxy)-(Z)-4-(3-methylbut-1-enyl)phenyl]benzofuran-6-ol (5). METHODS: The liquid microdilution assay was used in the determination of the minimal inhibitory concentration (MIC) and the minimal microbicidal concentration (MMC), against seven bacterial and one fungal species. RESULTS: The MIC results indicated that ACB as well as compounds 4 and 5 were able to prevent the growth of all tested microbial species. All other compounds showed selective activities. The lowest MIC value of 64 μg/ml for the crude extract was recorded on Staphylococcus aureus ATCC 25922 and Escherichia coli ATCC 8739. The corresponding value of 32 μg/ml was recorded with compounds 4 and 5 on Pseudomonas aeruginosa PA01 and compound 5 on E. coli ATCC 8739, their inhibition effect on P. aeruginosa PA01 being more than that of chloramphenicol used as reference antibiotic. CONCLUSION: The overall results of this study provided supportive data for the use of A. communis as well as some of its constituents for the treatment of infections associated with the studied microorganisms.